Multilevel multiresonator chipless radio frequency identification tags with high encoding capacity - Ibrahim, Omar Jabbar (2016)
Automatic Identification procedures (Auto-ID) have become very popular in recent years. They are used to provide information about people, animals, goods, and products in transit or in storage. Barcodes and RFID (Radio Frequency Identification) are the two widely used identification systems. Chipless RFID owing to its low cost has opened a new era for the identification world. There are not a lot of chipless RFID tags available in the market. However, due to the low cost, these tags started to conquer a part of the market. Several constraints such as coding capacity, miniaturization, cost per tag, printable designs, etc. need to be considered while developing chipless tags. This thesis reviews the existing chipless tags and also presents the design, fabrication, and measurement of two different types of multiresonator based chipless RFID that operates within the UWB (Ultra-Wide Band) region (3.1-10.6GHz). It is an attempt to improve the performance of multiresonator based chipless RFID in terms of coding capacity. The tags have a CPW (Coplanar Waveguide) structure. The uniplanar property of the proposed tags makes these tags fully printable which simplifies the production process. Thus, the proposed tags are suitable for short ranged tagging of paper and plastic based items, such as paper documents and banknotes.First, an 8-bits B2L (Base-Two Levels) chipless tag that comprises two half-disc UWB monopole antennas and a B2L multiresonatoris presented. The multiresonator has a CPW structure with two types of resonators (Res-1 and Res-2) to create stop bands in the UWB spectrum. One type (Res-1) is placed on the center conductor, while the other (Res-2) is placed on the two sides of the ground plane. The use of the ground plane resonators enables the CPW to overcome the disadvantage of low bit density so that it increased the number of tag IDs by 1024 times than the reported tags. Distance measurements of the phase of the tag’s insertion loss show a successful detection at a distance of (50 cm). Second, two designs of B3L (Base-Three Levels) chipless multiresonators circuits (MR-a and MR-b) to develop a B3L chipless RFID tag are designed. These tags are spectral signature-based chipless tags in which a resonant structure is used to encode data into three coding levels (0, 1, and 2) instead of the conventional two coding levels (0 and 1). Simulation results showed that MR-a (embedded with Res-1 and Res-2 resonators) has a better performance than the MR-b (embedded with Res-3). Therefore, the MR-a and UWB antennas have been fabricated and integrated with each other to form the B3L chipless tag. Distance measurements showed a successful detection for the three levels was at a distance of 20 cm. The use of B3L chipless tag makes it possible to increase the number of tags’ IDs by 17 times than the reported tags. This tag occupies half the bandwidth occupied by other reported tags, therefore, only part of the UWB spectrum (3.1-7GHz) can be used for coding and the upper region of the UWB spectrum can be avoided since it contains spurious resonances that may cause detection error.